2011
DOI: 10.1017/s0142716411000051
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual parents' modeling of pragmatic language use in multiparty interactions

Abstract: Parental input represents an important source of language socialization. Particularly in bilingual contexts, parents may model pragmatic language use and metalinguistic strategies to highlight language differences. The present study examines multiparty interactions involving 28 bilingual English- and Marathi-speaking parent-child pairs in the presence of monolingual bystanders (children’s mean ages: 3;2 and 4;6). Their language use was analyzed during three sessions: parent and child alone, parent and child wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 45 publications
3
16
0
Order By: Relevance
“…At 20M most research assistants communicated with mothers in Dutch. The Tare and Gelman (2011) findings would suggest that mothers who mainly addressed their children in Dutch would stick to just Dutch if the research assistant’s language persona was an important factor, and that French-speaking mothers would be more likely to use Dutch utterances in their CDS during the recordings. The data do not support this conclusion: only five Dutch-speaking mothers stuck to using only Dutch (and 12 mainly Dutch-speaking mothers used some French as well), whereas the majority of French-speaking mothers (nine) used only French, and only six mainly French-speaking mothers also used some Dutch.…”
Section: Results Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At 20M most research assistants communicated with mothers in Dutch. The Tare and Gelman (2011) findings would suggest that mothers who mainly addressed their children in Dutch would stick to just Dutch if the research assistant’s language persona was an important factor, and that French-speaking mothers would be more likely to use Dutch utterances in their CDS during the recordings. The data do not support this conclusion: only five Dutch-speaking mothers stuck to using only Dutch (and 12 mainly Dutch-speaking mothers used some French as well), whereas the majority of French-speaking mothers (nine) used only French, and only six mainly French-speaking mothers also used some Dutch.…”
Section: Results Summary and Discussionmentioning
confidence: 99%
“…Tare and Gelman (2011) showed that in interactions with their children bilingual mothers limited their use of a language that was not spoken by a monolingual investigator who was silently present during the recordings (thus, for instance, they spoke relatively less Marathi when an investigator they believed did not speak any Marathi was present than when a bilingual Marathi-speaking investigator or no investigator was present). The findings in the present study do not correspond to these results, because mothers were less apt to use two languages in the presence of a bilingual investigator (at 53M) and more apt to use two languages in the presence of a research assistant they had only heard using a single language (at 20M).…”
Section: Results Summary and Discussionmentioning
confidence: 99%
“…The final study found that unlike their parents, 3- and 4-year-old DLLs did not adjust their language to the language of a third-party when engaged in a conversation. Children tended to use English, which was the language of their schooling (Tare & Gelman, 2011). …”
Section: Resultsmentioning
confidence: 99%
“…This ability to use the appropriate code with the appropriate person in the appropriate setting has long been demonstrated by young bi-/multilinguals who are able to use the relevant language in relation to their interlocutors and context (see e.g. Deuchar and Quay 1999;Paradis and Nicoladis 2007;Tare and Gelman 2011).…”
Section: Discussionmentioning
confidence: 99%